The Influence Of Online Promotion And Discounts On Impulse Buying In Consumers Of Matahari Department Stores Store Binjai Supermall - Indawati Lestari; Hasbiana Dalimunthe (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to determine and analyze the effect of online promotion and discounts on impulse buying at Matahari Binjai Supermall consumers. Sample withdrawal using accidental technique. The number of samples taken was 150 respondents. Data processing using multiple linear regression. The results showed that online promotion has a positive and significant effect on impulse buying, discounts have a positive and significant effect on impulse buying. Simultaneously online promotion and discounts have a positive and significant effect on impulse buying.